Risks and consequences of the misuse of pesticides in the treatment of stored products - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Risks and consequences of the misuse of pesticides in the treatment of stored products Technical leaflet No 2 September 1996 19pp